2016
DOI: 10.1080/10803548.2016.1190233
|View full text |Cite
|
Sign up to set email alerts
|

Arabian, Asian, western: a cross-cultural comparison of aircraft accidents from human factor perspectives

Abstract: Although not given much consideration, national culture can have an impact on aviation safety. This study revealed that national culture plays a role in aircraft accidents related to human factors that cannot be disregarded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…<insert Figure 8 about here> A total of 10 (23.3%) studies in the civil and/or military aviation context reported the frequency of the presence of a HFACS category (Wiegmann and Shappell, 2001;Gaur, 2005;Li and Harris, 2006;Shappell et al, 2007;Lenne et al, 2008;Li et al, 2008;Hooper and O'Hare, 2013;Li and Harris, 2013;Daramola, 2014;Al-Wardi, 2017) (Figure 9). The weighted mean proportions and standard deviations of 18 HFACS categories are based on 2,813 accidents (i.e., 47.2% of the total accidents analysed).…”
Section: Hfacs Classificationsmentioning
confidence: 99%
“…<insert Figure 8 about here> A total of 10 (23.3%) studies in the civil and/or military aviation context reported the frequency of the presence of a HFACS category (Wiegmann and Shappell, 2001;Gaur, 2005;Li and Harris, 2006;Shappell et al, 2007;Lenne et al, 2008;Li et al, 2008;Hooper and O'Hare, 2013;Li and Harris, 2013;Daramola, 2014;Al-Wardi, 2017) (Figure 9). The weighted mean proportions and standard deviations of 18 HFACS categories are based on 2,813 accidents (i.e., 47.2% of the total accidents analysed).…”
Section: Hfacs Classificationsmentioning
confidence: 99%
“…Instead, the proportionate number of fatal accidents varied significantly and to an extent that cannot immediately be explained by differences in reporting practices. Previous research has shown that national culture can play a role in aircraft accidents related to human factors [19]; future work may investigate whether safety cultures and regulation differences provide a better explanation of the results of this study and whether they should be the focus of improvement in ultralight aviation practices.…”
Section: Discussionmentioning
confidence: 88%
“…Chen et al used HFACs to study the cause of ship collision accidents, and found that human and organizational factors have more significant impact on the occurrence probability [9], while Zhang et al used HFACs to investigate the contributing factors of major road traffic accidents and found that unsafe acts, violations, and inadequate regulations are the most important factors [10]. Similar researches also exist in various fields, such as maritime [11][12][13], coal mine [14][15][16], aviation [17][18][19], transportation [20][21][22], construction [23,24], and so on. Hulme et al [25] collected 43 studies, which analyzed the causes of accidents by HFACs from 2000 to 2018 and found there are 15 studies belong to the field of aviation, and there are 10, seven, six, and two studies belong to the field of maritime, mining, transportation, and construction, respectively.…”
Section: Introductionmentioning
confidence: 97%